2013
DOI: 10.1007/s10456-013-9338-9
|View full text |Cite
|
Sign up to set email alerts
|

Scleroderma Mesenchymal Stem Cells display a different phenotype from healthy controls; implications for regenerative medicine

Abstract: BM-MSCs from SSc patients behave as pericytes. They display a more mature and myofibroblast-like phenotype, probably related to microenvironmental cues operating during the disease. After their co-culture with HC-MVECs, SSc BM-MSCs underwent to a phenotypic modulation which re-programs these cells toward a pro-angiogenic behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 51 publications
1
48
0
Order By: Relevance
“…Further, we provided evidence of a profibrotic phenotype of human perivascular cells expressing increased levels of α-SMA and collagen during SSc 3,5 , and that SSc-EC may modulate the production of profibrotic molecules in perivascular dcSSc-MSC, thus eliciting a profibrotic phenotype 4 . The findings of ADAM12 hyperexpression and activation in SSc perivascular cells support the hypothesis of the profibrotic involvement of these cells during SSc.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Further, we provided evidence of a profibrotic phenotype of human perivascular cells expressing increased levels of α-SMA and collagen during SSc 3,5 , and that SSc-EC may modulate the production of profibrotic molecules in perivascular dcSSc-MSC, thus eliciting a profibrotic phenotype 4 . The findings of ADAM12 hyperexpression and activation in SSc perivascular cells support the hypothesis of the profibrotic involvement of these cells during SSc.…”
Section: Discussionmentioning
confidence: 75%
“…In dcSSc skin, the number of S100A4+/ADAM12+ FB surrounding the vessels was significantly higher than in HC 3 …”
Section: Adam12 Expression In Skin Dcsscmentioning
confidence: 74%
See 2 more Smart Citations
“…93 BM-MSCs from patients with SSc are similar to those from healthy donors in terms of their phenotype and capacity to differentiate into adipogenic and osteogenic lineages, 94 showed an upregulation of pericytespecific markers and a decreased proliferation capacity. 95 It has also been shown that SSc MSCs constitutively over-express and release pro-angiogenic mediators compared with healthy control MSCs. 96 In 2013 an open-label and single arm study was performed in 12 SSc patients in order to evaluate the number of adverse events related to SVF injection.…”
Section: Focus On Adscs Application For Wound Healing In Systemic Sclmentioning
confidence: 99%